Fenologia e biologia floral de Sapium glandulosum (L.) Morong 1893 (Euphorbiaceae) e suas interações ecológicas com artrópodes durante período reprodutivo em uma área de Cerrado - Cardoso, Renan Kobal de Oliveira Alves (2016)
This study aimed to add new knowledge about ecological interactions considering a recent colonization in palm swamp in Private Reserve of Clube de Caça e Pesca Itororó in Uberlândia city, Minas Gerais state, Brazil. We recorded 39 species of six insect orders visiting the branches of S. glandulosum. The most common were Hymenoptera followed by Diptera. The most common species was Syrphidae sp1 (Diptera) with 141 visits, followed by Polybia scutellaris (Hymenoptera) with 91 records. There was a high visitation of flies on the inflorescences, 49.2% in staminate flowers and 40.1% in pistillate flowers. Although, S. glandulosum proved to be a generalist entomophilous specie offering resources such as pollen and secretions from glands associated with flowers and extrafloral nectar. Neolithus fasciatus was the only species of herbivore observed, inducing galls mainly on leaves, but also on petiole and central axis of the inflorescences. The floral morphology of S. glandulosum does not fit the existing pollination syndromes. S. glandulosum has food resources for generalist insects and the ability to interact with specialized animals.